IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH PADA SISWA KELAS VA DI SD NEGERI 20 KAMPUNG LORONG TAHUN PELAJARAN 2023-2024 - Esti Aprilia; Ahmad Rathomi, Elsa Mulya Karlina (ADISAM PUBLISHER, 2024)
The aim of this research is to reveal: 1) The form of the School Literacy Movement (GLS) among VAA class students at SD Negeri 20 Kampung Lorong for the 2023-2024 academic year; 2) Stages of the School Literacy Movement (GLS) for class VA students at SD Negeri 20 Kampung Lorong for the 2023-2024 academic year; 3) Supporting and inhibiting factors for the School Literacy Movement (GLS) among class VA students at SD Negeri 20 Kampung Lorong for the 2023-2024 academic year. This research technique uses a qualitative approach with a phenomenological type of research. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation, and data conclusion. The results of the research show that the form of the School Literacy Movement at SD Negeri 20 Kampung Lorong 2022-2023 is in the form of a daily literacy movement and a weekly literacy movement. The daily literacy movement is carried out in the classroom using textbooks (Theme), while the weekly literacy movement is carried out outside the classroom, namely in the school library using non-textbooks or story books. The stages of implementing the School Literacy Movement at SD Negeri 20 Lorong village for the 2022-2023 academic year are the habituation stage, development stage and learning stage. These stages really help the process of school literacy activities, by following these three stages so that the School Literacy Movement program is implemented well. The supporting and inhibiting factors for the School Literacy Movement at SD Negeri 20 Kampung Lorong in improving students' reading abilities for the 2022-2023 academic year are as follows: a) Supporting factors, namely, facilities and infrastructure, reading materials. b) Factors inhibiting the literacy movement are, literacy habits are not yet a priority for students, a lack of reading books or reading resources, and activities that require concentration so that students get bored easily